1996
DOI: 10.2527/1996.744908x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary concentrate level on nutrient absorption, liver metabolism, and urea kinetics of beef steers fed isonitrogenous and isoenergetic diets.

Abstract: Six multicatheterized beef steers (421 +/- 21 kg BW) were used to predict the effect of dietary concentrate level on blood flow and net flux of urea and other metabolites across splanchnic tissues. Diets ranged from 0% (switchgrass hay) to 90% concentrate (10% switchgrass hay, 89% cracked corn, 1% urea). Daily DMI varied from 8.01 to 5.34 kg/d. Nitrogen intake (99 g/d) and calculated ME intake (16.8 Mcal/d) were equal among diets. As dietary concentrate increased from 0 to 90%, liver blood flow decreased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
39
4
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 23 publications
17
39
4
5
Order By: Relevance
“…the forage to concentrate ratio) and intake. Huntington et al (1996) reported that, when fed diets with 20% or less concentrate, steers recycled 90% of hepatic urea production; the percentage of recycled urea decreased to 64 with 63% of the diet as concentrates, and to 51% when diets with 90% concentrate were fed. Increased urea recycling to the GIT may improve the overall effi ciency of N utilization for maintenance and production.…”
Section: Manipulating Pathways Of Urea Recyclingmentioning
confidence: 99%
“…the forage to concentrate ratio) and intake. Huntington et al (1996) reported that, when fed diets with 20% or less concentrate, steers recycled 90% of hepatic urea production; the percentage of recycled urea decreased to 64 with 63% of the diet as concentrates, and to 51% when diets with 90% concentrate were fed. Increased urea recycling to the GIT may improve the overall effi ciency of N utilization for maintenance and production.…”
Section: Manipulating Pathways Of Urea Recyclingmentioning
confidence: 99%
“…This is due to the protein content of the hay harvested at 15 days of growth, which resulted in a higher amount of digestibility of crude protein and therefore a larger amount of nitrogen for the rumen. It is important to highlight that NH 3 -N contents directly relate to dietary CP amounts (Freeman et al, 1992;Huntington et al, 1996;Thivierge et al, 2002), a fact observed in this trial. Furthermore, it is worth mentioning that the activity of cellulolytic microorganisms is highly dependent on ruminal NH 3 -N concentration.…”
Section: Ruminal Fermentation Parametersmentioning
confidence: 99%
“…With increasing grain in the diet, there is also an increase in the amount of glucose absorbed postruminally (Huntington et al 1996). Taken together, these results indicate altering the forage:concentrate ratio likely results in different substrates available for absorption, for interaction with gastrointestinal epithelial cells, and for interaction with post-absorptive tissues.…”
Section: Discussionmentioning
confidence: 83%